Current Understanding of Interactions between Nanoparticles and ABC Transporters in Cancer Cells - Yin, Jian; Deng, Xudong; Zhang, Jie; Lin, Jun (Current Medicinal Chemistry, 2018)
Background: ATP-binding cassette (ABC) transporters-mediated multidrug resistance (MDR) remains the major obstacle for effective cancer therapy. Nanoparticles (NPs)-based delivery systems are promising to overcome MDR, but only a few of them have been accepted for clinical treatment, which should be due to their insufficient transportation and potential toxicity. In this respect, more and more attentions are being attracted on the interactions between NPs and ABC transporters, which hold a key role in the treatment of MDR cancer and the toxicity of NPs. However, there are no systematic reviews about such interactions, especially about their corresponding mechanism. Methods: We undertook extensive search of PubMed databases for peer-reviewed literatures using focused review questions. The retrieved papers were mostly published within the 5 years (84 of 104) and all with an impact factor above 2. First, this review focused on the current knowledge of ABC transporters involved in MDR and their inhibitors. Then, we reviewed the most recent literature about the inhibitory effects of organic NPs' excipients on ABC transporters and the direct interactions of inorganic NPs with ABC transporters. The major elements of obtained papers were described and classified depending on the structure of NPs. Results: Both organic and inorganic NPs can inhibit the function of ABC transporters, but based on different mechanisms. The effects of organic NPs are caused by several excipients like surfactants, polymers, lipids and cyclodextrin. Meanwhile, inorganic NPs usually act as the substrates of ABC transporters and competitively inhibit the efflux of drugs. These phenomena are interesting and worth investigating. Conclusion: The finding of this review confirmed the potential interactions between NPs and ABC transporters. These phenomena are interesting and worth investigating, and a knowledge of related mechanism would not only be important for the clinical therapies toward overcoming cancer MDR, but also help the treatment of other diseases like tuberculosis, AIDS, and central nervous system disorders, whose drugresistance was also related to ABC transporter-mediated efflux.
Keywords: organic nanoparticles